Pengaruh Motivasi Kerja Terhadap Produktivitas Pegawai pada Dinas Kepemudaan, Olahraga Dan Pariwisata Bidang Olah Raga Kabupaten Banyuasin - Riri Hanifa; Rindy Tara Armareta; Dina Rossi Utami; Frecilia Nanda Melvani (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study is entitled The Effect of Work Motivation on Employee Productivity at the Office of Youth, Sports and Tourism in the Sports Field of Banyuasin Regency.The formulation of the problem in this study is how does the influence of work motivation on the productivity of employees of the Youth, Sports and Tourism Office in the Sports Field of Banyuasin Regency. This study aims to identify the effect of work motivation on the productivity of employees of the Department of Youth, Sports and Tourism in the Sports Field of Banyuasin Regency. The samplingtechnique in this study used a saturated sampling technique with a total of 43 respondents. The data analysis technique is descriptive statistical analysis, data quality analysis, simple regression analysis, statistical test (t) and the coefficient ofdetermination (R2). The results of this study indicate that the partial hypothesis testof Work Motivation variable has a significant effect on Employee Productivity. Theresults of simple regression analysis show that the Work Motivation Variable has a positive effect on the Employee Productivity variable. The results of the analysis of the correlation coefficient and the coefficient of determination show that themotivation variable has a very strong relationship and influences employee productivity at the Sports Youth and Tourism Office in Banyuasin Regency.